2020
DOI: 10.1002/jctb.6321
|View full text |Cite
|
Sign up to set email alerts
|

Antarctic yeast Cryptococcus laurentii (AL65): biomass and exopolysaccharide production and biosorption of metals

Abstract: BACKGROUND Pollution by heavy metals poses serious environmental problems and is dangerous to human health, so considerable attention has been given to methods for their removal from industrial effluents. The need for highly effective biosorbents able to remove heavy metals from waste waters, even at the low concentrations which are still toxic for living organisms in ecosystems, is a topical problem. RESULTS In the present study, psychrophilic yeast strain Cryptococcus laurentii (AL65) was used to explore its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Downstream processing technologies such as recovery, purification, and characterization in developing bioinoculants do not require high resolution techniques presumably due to their environmental purpose, thus purification steps are not necessarily required. Thus, filamentous and yeast bioinoculants can be adequately recovered by unit operations involving solid/liquid separation such as filtration and centrifugation [41,185]. However, the application of drying techniques can increase the storage feasibility and shelf life of metabolically inactive bioinoculants compared to those with active metabolism.…”
Section: Downstream Processing: Efficiency Ecotoxicological Safety Re...mentioning
confidence: 99%
See 1 more Smart Citation
“…Downstream processing technologies such as recovery, purification, and characterization in developing bioinoculants do not require high resolution techniques presumably due to their environmental purpose, thus purification steps are not necessarily required. Thus, filamentous and yeast bioinoculants can be adequately recovered by unit operations involving solid/liquid separation such as filtration and centrifugation [41,185]. However, the application of drying techniques can increase the storage feasibility and shelf life of metabolically inactive bioinoculants compared to those with active metabolism.…”
Section: Downstream Processing: Efficiency Ecotoxicological Safety Re...mentioning
confidence: 99%
“…In this sense, dimorphic fungi (e.g., black fungi) in their filamentous structure may be more viable to be applied as bioinoculants, because hyphae can penetrate into the contaminated soil matrix pores, which allows greater accessibility and permeation to contaminants between different regions of the mycelium and through the air [101,182]. On the other hand, dimorphic fungi in their yeast-like form may be more viable to be applied in bioprocesses as producers of metabolites to be applied in mycoremediation, because the yeast morphology facilitates biomass recovery [185].…”
mentioning
confidence: 99%
“…Recently biosorption has gained much attention, as this technology utilizes materials or sorbents of biological origin, including bacteria, fungi, yeast, algae, and agricultural wastes. Biosorbents have the capacity to bio-accumulate or adsorb the metals to their surfaces (Rusinova et al, 2020). They can effectively sequester dissolved metal ions out of dilute complex solutions with high efficiency and quickly.…”
Section: Introductionmentioning
confidence: 99%
“…It has been documented that EPSs obtained from microorganisms find application in areas, such as health, cosmetics, food, and bioremediation. EPS‐producing microorganisms include bacteria, archaea, microalgae, yeasts, and molds 2,4–6 . For example, it has been reported that bacterial strains belonging to genera such as Alcaligenes, Alteromonas, Bacillus, Cobetia, Colwellia, Flavobacterium, Geobacillus, Halomonas, Hyphomonas, Lactobacillus, Leuconostoc, Pseudoalteromonas, Pseudomonas, Rhizobium, Rhodococcus, Shewanella, Sphingomonas, Streptococcus, Vibrio, Xanthomonas, Zooglea , and Zymomonas are capable of producing EPS 6,7 …”
Section: Introductionmentioning
confidence: 99%